Metode Tutor Sebaya Terhadap Hasil Belajar Kognitif Matematika Siswa Madrasah Aliyah Kelas X - Muhammad Farid Nasrulloh; wisnu siwi satiti; Huurun A'in - (Universitas KH. A. Wahab Hasbullah, 2019)
This research as a purpose to understand the effect a peer tutor learning method about the results of learning cognitive math of students X class at main materialssystem of linear equation three variables. This research belong quantitative descriptive research. Subject of the research is student X class at MA Assulaimaniyyah Mojoagung Jombang as many as 30 students.The research has carried on only one category without a group of a comparison. The data collecting use question test and math results learning outcomes at other materials was learned by teacher at that school. That other materialsislinier equation and inequality a value of absolute one variables.The results of learning at other materials as a purpose to understand the first condition of student while results of learning cognitive math as a purpose to understanding change condition. Analysis of the data using t-test and a significance level of = 0,05. The results of data analysis using t-test obtained t = 6,743 and table = 2,045 at significance level of 5%.It means that there were significant peer tutoring methods to the result of learning cognitive math of student X class at materials system of linear equation three variables in MA Assulaimaniyyah.